VALEOLOGY - A BRANCH OF HEALTH SCIENCE ABOUT HEALTHY PEOPLE: AN INTERDISCIPLINARY SCIENCE (Fiep Bulletin - online, 2014)
Valeology is a science about formation mechanisms, maintenance and strengthen of the human being Health in ontogenesis. Valeology is a new direction in science area about human being. If the medicine is oriented to treat the human being organism (to get out of illness) with the utilization of several drugs and surgery procedures, the Valeology has the purpose to combine the vital system working of organism through development of its organic systems by means of Physical Education, Pedagogy, Sport Medicine, scientific knowledge in the areas of physiology, biochemistry, differential psychophysiology, psychology, biology, ecology, pedagogy, physical education, nutrition, sports medicine and philosophy. Therefore, its purpose is also to elaborate instruments and methodologies of organism alteration diagnostic before clinic diagnostic of illness realized by a doctor.
Keywords: Valeology; Individual Health; Human organism